A Review of the Channel Modeling Characteristics and Techniques for Body Area Network - AL-Asadi, Ahmed Mohammed Q.; Wadday, Ahmed Ghanim (Current Approaches in Science and Technology Research Vol. 6, 2021)
Human voxel phantoms communications presently a committed fielded for wireless body area network (WBAN). Channel flexibility and characteristics depend on the required environments and the situations of the body. There are many challenges to employing the sensors to the patient concerning the telecom techniques during the use of simulation such as the position of antennas on the body surface and inside the human. It causes inaccuracies and uncertainty in the system. There are several numerical solutions convenient for employ in wireless body networks and modeling the simulation. The synopsis of this paper is based on neoteric searches in the techniques used for the WBA communication channel. Routing classification, wireless technologies, advantages, and disadvantages foremost acceptable application techniques are demonstrated and compared.